Research progress in regulation of residual stress and distortion in wire arc additive manufacturing - LI Xuan; CHEN Yong; CHEN Hui; XIONG Jun (Cailiao gongcheng)
Wire arc additive manufacturing （WAAM） employs an arc as the energy source to melt metal wire layer by layer， making it suitable for the rapid fabrication of medium to large-sized complex metal components. Owing to its high forming efficiency， low manufacturing costs， and exceptional material utilization rates， WAAM has extensive application prospects in the aerospace and defense sectors. The regulation of residual stress and distortion in metal components is a key scientific and technical problem that must be solved to promote the efficient and high-quality development and application of WAAM. The mechanisms and influencing factors of residual stress and distortion in WAAM are explored. The experimental measurement and numerical simulation methods are analyzed and compared， and strategies for reducing residual stress and distortion at different stages of the WAAM process （before， during， and after deposition） are systematically summarized. Finally， it is pointed out that numerical simulations， machine learning， in-situ diagnosis， and control are the key research directions for controlling residual stress and distortion in WAAM in the future.